The merry matchmaker - Roberts, Sheila, 1951- (Mira, 2024)
Inspired by Jane Austen's Emma, this joyful Christmas romp tells the story of a woman who can't stop trying to help everyone around her find their happily-ever-after--even when her help leads to disaster. Frankie Lane knows what's best for just about everyone but herself. Her divorced sister, Stef, who is too young to give up on love; her shy employee, Elinor; and her daughter, Natalie, who works in Frankie's shop, Holiday Happiness, and really needs to start her own business selling the delectable chocolates she makes at home; even her best friend, Viola, who is trying to renovate her old Victorian. Frankie knows she could help all of them, if they'd just let her--and if all of her help didn't end in utter disaster. Then there's Mitch Howard, the owner of the local hardware store. They've been friends ever since Frankie opened her store, nine years earlier. He got her through the nightmare when she lost her husband in a freak accident, and he's her favorite shoulder to cry on. He's been divorced for years, and it's such a waste of man! Mitch is the fittest, finest man Frankie knows. He's easygoing, wise and kindhearted. Mitch needs someone. And she's determined to help him find that someone--whether he likes it or not. --